Molecular genetic and cytogenetic determinants of primary resistance or loss of the response to treatment with tyrosine kinase inhibitors in patients with chronic myeloid leukemia. - K. Kotlyarchuk; Z. Maslyak; A. Lukianova; O. Tsyapka; I. Selina; A. Usenko (Medičnì Perspektivi)
Aim of this study was to analyze molecular genetic and cytogenetic reasons for disease resistance to tyrosine kinase inhibitors (TKI) imatinib (IM) and nilotinib (NI) in patients with chronic myeloid leukemia (CML). Material and methods. A group of 32 CML patients with primary or acquired resistance to TKI treatment was investigated. Cytogenetic response was determined by conventional karyotyping with differential banding. Presence of BCR-ABL kinase domain mutations was investigated by direct sequencing. Results and discussion. The frequency of mutations was 37% (12 patients) with prevailing occurrence of mutations with low sensitivity to nilotinib – E255K/V; Т315I; F359V; Y253H. In 47% of the cases (15 patients) additional chromosome aberrations (ACA) were revealed which could also be the reason for TKI resistance in patients without BCR/ABL mutations. Patients with detected mutations of BCR/ABL gene were either switched to nilotinib or treated with increased dose of IM. Cytogenetic response was achieved in only 2 patients with mutations and in 12 patients without them. Frequency of blast crisis development did not differ significantly in both groups. Conclusions. Among the investigated patients with CML resistant to IM BCR/ABL gene mutations were detected in more than third of the cases whereas ACA were found in almost half of the group. Taking into account revealed prevalence of mutations not sensitive to the 2nd generation TKI nilotinib, investigation of mutational status has to be obligatory in all patients for whom treatment correction is considered. Presence of ACA should also be taken into account in patients requiring administration of the second line TKI since they can adversely influence expected treatment response as well.